Poverty and development in Tanzania - Riccardo Pelizzo; Lucas Katera; Stephen Mwombela; Lulu Olan'g (African Governance and Development Institute (AGDI), 2018)
The paper investigates the relationship between development, as measured by the GNI per capita and lived poverty in Tanzania which is measured on the basis of whether and how often respondents go, in the course of one year, without food, water, medical care, cooking fuel and cash income. By using the data collected by Afrobarometer in Tanzania, we are able to create one set of indicators that capture the extension of lived poverty, that is what percentage of the respondents, experiences deprivation, but we also develop a series of indicators that capture the severity of lived poverty, that is how frequently respondents experience this problem. Our statistical analyses reveal that while Tanzanian progress along the developmental path did not have a significant impact on the extension of lived poverty, it made a large and significant contribution to reduce its severity.
Keywords: O40; O57; I10; I20; I32; 330; poverty; lived poverty; Afrobarometer; development; inequality; Tanzania